2010
DOI: 10.1111/j.1399-6576.2010.02253.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury with renal replacement therapy in trauma patients

Abstract: AKI in trauma patients requiring RRT was rare in this single-center study. More males than females were affected. Mortality was modest, and renal recovery was excellent as none of the survivors became dependent on chronic RRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…Renal recovery was similar to that previously reported in military casualties (1)(2)(3)5,(7)(8)(9). In civilian series, .90% of patients recover renal function before discharge, even though many had comorbidities that increased ESRD risk (10)(11)(12)14,29,30).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Renal recovery was similar to that previously reported in military casualties (1)(2)(3)5,(7)(8)(9). In civilian series, .90% of patients recover renal function before discharge, even though many had comorbidities that increased ESRD risk (10)(11)(12)14,29,30).…”
Section: Discussionsupporting
confidence: 84%
“…Observed mortality is approximately 40%-80% in civilian trauma series (10)(11)(12)29,30). Preexisting chronic conditions and increasing age have been associated with higher mortality in some series (10,12), However, Machemehl et al reported mortality was independent of age, albeit in an older population with comorbidities (13). Among children in the Prospective Pediatric CRRT registry, mortality was 42%, but PTAKI was not a reported cause of AKI (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3561219] We found that median (IQR) LOS was 5.5 (1-53) days ( P = 0.001) in the control group as compared to 9 (1, 83) days in the renal failure group. Also ISS was found to be higher in control group (20.4 ± 8.5) than in the non-renal failure groups (13.3 ± 6.0) with P value < 0.001.…”
Section: Discussionmentioning
confidence: 95%